Responses of intramembranous bone and sutures upon in vivo cyclic tensile and compressive loading - Peptan, Alexandra I. (2007)
Cranial vault and facial sutures interpose between mineralized bones of the skull, and may function analogously to appendicular and cranial base growth plates. However, unlike growth plates that are composed of chondrocyte lineage, cranial and facial sutures possess heterogeneous cell lineages such as mesenchymal cells, fibroblasts, and osteoblasts, in addition to vascular-derived cells. Despite recently intensified effort, the biological responses of intramembranous bone and sutures to mechanical loading are not well understood. This study was designed to investigate whether brief doses of tensile or compressive forces induce modeling and growth responses of intramembranous bone and sutures. In different groups of growing rabbits in vivo, cyclic tensile or compressive forces at 1 Newton and 8 Hz were applied to the maxilla for 20 min/d over 12 consecutive days. Computerized histomorphometric analyses revealed that the average sutural widths of both the premaxillomaxillary suture (PMS) and nasofrontal suture (NFS) loaded in either tension or compression were significantly higher than age- and sex-matched sham controls (P<0.01). The average cell density of tension- or compression-loaded PMS and NFS were significantly higher than sham controls (P<0.01). The average osteoblast occupied sutural bone surface loaded under tension was significantly higher than that of sham control (P<0.05). Interestingly, tensile loading significantly reduced the average osteoclast surface, in comparison to sham control (P<0.05). For the NFS, tensile loading significantly increased the average osteoblast occupied sutural bone surface, in comparison with that of sham control (P<0.05). Also for the NFS suture, compression significantly reduced the average sutural osteoclast surface in comparison with sham control (P<0.05). Taken together, the present data suggest that high-frequency cyclic forces in either tension or compression induce modeling and growth changes in cranial sutures. Due to the structural complexity of cranial vault and facial sutures, either tensile or compressive forces likely are transmitted as shear stresses and upregulate genes and gene products responsible for sutural growth.